PTEN loss drives resistance to the neddylation inhibitor MLN4924 in glioblastoma and can be overcome with TOP2A inhibitors. Issue 11 (19th March 2022) - Ferdosi, Shayesteh R; Taylor, Brett; Lee, Matthew; Tang, Nanyun; Peng, Sen; Bybee, Rita; Reid, George; Hartman, Lauren; Garcia-Mansfield, Krystine; Sharma, Ritin; Pirrotte, Patrick; Ma, Jianhui; et al.
Abstract: Background: Neddylation inhibition, affecting posttranslational protein function and turnover, is a promising therapeutic approach to cancer. We report vulnerability to MLN4924 or pevonedistat (a neddylation inhibitor) in a subset of glioblastoma (GBM) preclinical models and identify biomarkers, mechanisms, and signatures of differential response. Methods: GBM sequencing data were queried for genes associated with MLN4924 response status; candidates were validated by molecular techniques. Time-course transcriptomics and proteomics revealed processes implicated in MLN4924 response. Results: Vulnerability to MLN4924 is associated with elevated S-phase populations, re-replication, and DNA damage. Transcriptomics and shotgun proteomics depict PTEN signaling, DNA replication, and chromatin instability pathways as significant differentiators between sensitive and resistant models. Loss of PTEN and its nuclear functions is associated with resistance to MLN4924. Time-course proteomics identified elevated TOP2A in resistant models through treatment. TOP2A inhibitors combined with MLN4924 prove synergistic. Conclusions: We show that PTEN status serves as both a novel biomarker for MLN4924 response in GBM and reveals a vulnerability to TOP2A inhibitors in combination with MLN4924.